(untitled) (Perner’s Contacts, 2010)
The aim of this contribution is verification of hypothesis, which speaks aboutmutual influence of transport and economical system in various time horizons. Theresearch basis with partial hypothesis is interactive relation model of transport andeconomical system. Verification of this hypothesis is based on mathematicalmodelling by usage of statistical methods working with selected key indicators ofboth systems.